Cotard Syndrome without Depressive Symptoms in a Schizophrenic Patient - Pedro Morgado; Ricardo Ribeiro; João J. Cerqueira (Case Reports in Psychiatry)
Introduction. Cotard syndrome is a rare condition characterized by nihilistic delusions concerning body or life that can be found in several neuropsychiatry conditions. It is typically associated with depressive symptoms. Method. We present a case of Cotard syndrome without depressive symptoms in the context of known paranoid schizophrenia. A literature review of Cotard syndrome in schizophrenia was performed. Results. Although there are few descriptions of this syndrome in schizophrenia, patients usually present depressive mood and psychomotor retardation, features not seen in our patient. Loss of the sense of the inner self, present in schizophrenia, could explain patient’s symptomatology but neurobiological bases of this syndrome remain unclear. Conclusion. Despite not being considered in actual classifications, Cotard syndrome is still relevant and psychiatric evaluation is critical to diagnosing and treating this condition in psychiatric patients.